Evaluation of Length and Fiber Count Determinations for Natural and Synthetic Microfibers Using the OpTest Fiber Quality Analyzer - Michael Santiago Cintron; Chanel A. Fortier; Sunghyun Nam (Microplastics)
Microfibers are small fiber particles that range from 1 µm to 5 mm in length, generated through the home laundering and daily wear of textile garments. Microfibers stemming from synthetic textiles are a global pollution problem marked by their slow biodegradation and steady environmental accumulation. Thus, the quantification and study of factors controlling their generation is of interest. The aim of the current study included exploring the use of a Fiber Quality Analyzer-360 (FQA) for examining fiber counts and lengths of microfibers derived from cotton, flax, ramie, hemp, acrylic, polyester, viscose, and polyamide, and to explore if additional preparation steps, such as sonication, would improve microfiber detection by the system. While probe sonication led to higher fiber counts for most microfiber types, average microfiber lengths were statistically similar for most samples, with only the hemp and ramie samples showing statistically shorter microfibers following sonication. FQA detection estimates for cotton, viscose, and ramie microfibers were high, at 99, 101, and 116% for viscose, flax, and cotton, respectively. In contrast, synthetic microfibers of acrylic, polyamide and polyester showed 77, 43, and 14% detection rates, respectively. The high detection rate for the cotton sample is partly due to the higher fineness value obtained from the gravimetric determination. A similar calculation using AFIS fineness showed 86% detection. These observations confirm the significance of properly suspending the samples to accurately quantify microfibers while using the FQA system. Furthermore, the reduced detection of the examined synthetic microfibers suggests the limitations of the FQA as a technique for the direct comparison of natural and synthetic microfiber counts.